Closed-loop deposition of martensitic stainless steel during laser additive manufacturing to control microstructure and mechanical properties. (October 2021) - Farshidianfar, M.H.; Khodabakhshi, F.; Khajepour, A.; Gerlich, A.P.
Highlights: A new closed-loop laser additive manufacturing (LAM) system was developed. The melt pool temperature and cooling rate were controlled in real-time. The layer-upon-layer deposition treatment was monitored by adaptive changing of laser traveling speed. Martensitic phase transformation studied depending upon the controlled constant cooling rate. Abstract: A closed-loop laser additive manufacturing (CLAM) system was developed to monitor and control layer-by-layer fabrication via directed energy deposition (DED). The well-modified laser additive manufacturing (LAM) package utilizes a thermal infrared camera and thermal image processing algorithms to extract and control the thermal dynamics of the process, including ( i ) cooling rate, ( ii ) melt pool temperature, and ( iii ) heating rate. Martensitic stainless steel of grade S410-L was used to cumulatively deposit 5 layers on top of each other at different processing conditions without closed-loop control. Significant deviations of cooling rate and melt pool temperature are observed within different layers of a thin-wall structure without feedback control in the open-loop state. To assess the effects of cooling rate control on final LAM properties, three samples with different setpoint cooling rates of 550, 1100, and 1750 °C/s are tested under closed-loop conditions. Microstructural and microhardness maps and profiles of open-loop and closed-loop samples reveal highly uniform and controlled hardness profiles when closed-loop control is applied, in contrast to highly varying properties in samples produce in open-loop operation. The current research results illustrate how one can achieve controlled microstructural characteristics and mechanical properties through real-time control of the cooling rate during the LAM process.